Vitamin Nature: How Coronavirus Disease 2019 Has Highlighted Factors Contributing to the Frequency of Nature Visits in Flanders, Belgium - Lenaerts, Aline; Heyman, Sofie; De Decker, Annelies; Lauwers, Laura; Sterckx, Ann; Remmen, Roy; Bastiaens, Hilde; Keune, Hans (Frontiers in Public Health, 2021)
Visiting nature is positively associated with physical and mental well-being. The role of nature became more pronounced during the coronavirus outbreak in the spring of 2020. Countries all over the world implemented confinement measures to reduce the transmission of the virus. These included but were not limited to the cancelation of public events, schools, and non-essential businesses and the prohibition of non-essential travels. However, going outside to exercise was recommended by the Belgian government. During this period, we conducted an online survey to determine if people visit nature more frequently than before and to identify the factors that contribute to this. The results are based on data from 11,352 participants in Flanders, Belgium. With the use of a bivariate and multiple regression analysis, results indicate that people visit nature more frequently than before and that nature helped to maintain social relationships during the coronavirus period. Gardens were reported to be the most popular place, followed by parks. More than half of the people experienced nature in a more positive way, and the belief that nature visits are important for general health increased. In addition, we found a positive association between nature visits and home satisfaction, as well as a positive association with subjective mental and physical health. Lastly, we identified several demographic factors contributing to the frequency of nature visits such as age, gender, and socioeconomic status. Our findings indicate the importance of nature visits for general well-being and highlight the need for nearby green infrastructure.